Alvimopan for prevention of postoperative paralytic ileus in radical cystectomy patients: a cost‐effectiveness analysis. (21st November 2012) - Hilton, William M.; Lotan, Yair; Parekh, Dipen J.; Basler, Joseph W.; Svatek, Robert S.
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? No cost‐effectiveness studies exist in patients after radical cystectomy for the routine use of alvimopan for the prevention of postoperative ileus. The present study provides a reasonable estimate of the cost‐effectiveness of alvimopan for the prevention of postoperative ileus in the patient after radical cystectomy. Objective To determine if the cost of administering alvimopan, to help restore bowel function after abdominal surgery, to all patients undergoing radical cystectomy (RC) is cost prohibitive. Patients and Methods A cost‐effective analysis was conducted from a healthcare payer perspective using a decision‐tree model that incorporated direct healthcare costs and probabilities associated with the possible events and outcomes. Sensitivity analyses were conducted on the influence of the cost and effectiveness of the drug, the probability of POI in RC patients, and the extended length of stay (LOS) as a result of POI. Precision in estimates was determined using probabilistic sensitivity analyses with 5000 Monte‐Carlo simulations. Results Under the base case assumption, the additional cost of a patient's LOS related to POI was 10 246 per person. Under the assumption that 15.6% of patients will have POI, the mean cost associated with POI in a cohort of patients not treated with alvimopan was 1597 (90% confidence interval [CI] 1335–1875) per patient. Conversely, the routine use of alvimopan for all patients undergoing RC was associated with a mean POI‐associated cost of 1495(90% CI 1312–1696) per person, which represents the cost of alvimopan (700 per hospitalisation) and a 50% reduction in the rate of POI. Sensitivity analyses revealed that there is a cost savings with the routine use of alvimopan under the following conditions: the POI results in extending LOS by ≥3.5 days, POI occurs in ≥14% of patients undergoing RC, or the drug results in a relative risk reduction of ≥44%. Conclusions Routine use of perioperative alvimopan may not be cost prohibitive because of its influence on POI rate and associated costs. The cost‐effectiveness of alvimopan is influenced by the POI incidence and the degree to which the drug can decrease the LOS.